Doped Organic Micro‐Thermoelectric Coolers with Rapid Response Time. (2nd August 2022) - Wang, Shu‐Jen; Wohlrab, Steve; Reith, Heiko; Berger, Dietmar; Kleemann, Hans; Nielsch, Kornelius; Leo, Karl
Abstract: Local thermal management has important implications regarding comfort, energy consumption, and electronic device performance/lifetime. While organic thermoelectrics have emerged as promising materials for flexible thermoelectric energy harvesting devices, their potential as Peltier cooling element has been largely overlooked. Here, micro‐thermoelectric coolers based on doped small molecule thin‐films with a fast response time (around 25 µs) which is among the fastest micro‐thermoelectric coolers reported are presented. This experimental cooling performance is supported by simulation using the finite‐element method for thermal transport. The results show that organic thermoelectrics offer great potential for flexible and wearable micro‐thermoelectric cooling applications. Abstract : While organic thermoelectrics have emerged as promising materials for flexible thermoelectric energy harvesting devices, their potential as Peltier cooling element remains largely unexplored. Here, micro‐thermoelectric coolers based on doped small molecule thin‐films are presented with a fast response time (around 25 µs) which is among the fastest micro‐thermoelectric coolers reported.